2019
DOI: 10.1126/sciadv.aaw0120
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing superconductivity in SrTiO 3 films with strain

Abstract: The nature of superconductivity in SrTiO3, the first oxide superconductor to be discovered, remains a subject of intense debate several decades after its discovery. SrTiO3 is also an incipient ferroelectric, and several recent theoretical studies have suggested that the two properties may be linked. To investigate whether such a connection exists, we grew strained, epitaxial SrTiO3 films, which are known to undergo a ferroelectric transition. We show that, for a range of carrier densities, the superconducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 46 publications
6
132
0
Order By: Relevance
“…The T C values [ Fig. 1(a)] are in agreement with values previously reported for strained, doped films on LSAT [28]. Enhanced T C values (up to 600 mK) near the peak of the superconducting dome relative to unstrained, doped SrTiO 3 are directly connected to the ferroelectric normal state, as shown elsewhere [28,29].…”
supporting
confidence: 89%
“…The T C values [ Fig. 1(a)] are in agreement with values previously reported for strained, doped films on LSAT [28]. Enhanced T C values (up to 600 mK) near the peak of the superconducting dome relative to unstrained, doped SrTiO 3 are directly connected to the ferroelectric normal state, as shown elsewhere [28,29].…”
supporting
confidence: 89%
“…The superconducting critical temperatures, measured in Ref. 17, are for the same films studied in this work. The phase diagram shows the well-known superconducting "dome" [1] in close proximity to the quantum critical point of the spontaneous ferroelectric order.…”
Section: Interplay Between Ferroelectricity and Superconductivitymentioning
confidence: 93%
“…Further details of film growth and transport measurements are described in Ref. 17. Optical SHG experiments were performed using an ultrafast laser supplying 40-fs pulses at a 10-kHz repetition rate and a center wavelength of 800 nm.…”
Section: Samarium-dopedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Raman scattering found that the hardening of the FE soft mode in the dilute metal is indistinguishably similar to what is seen in the insulator [21]. The anomaly in resistivity was found to terminate at a threshold carrier density (n * ), near which the superconducting transition temperature was enhanced [21] providing evidence for a link between superconducting pairing and ferroelectricity, a subject of present attention [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%